Thermal Analysis of the Encapsulation of Resonance Circuit Modules for the Paving Into Electric Road Systems - Kneidl, Maximilian; Kneidl, Maximilian; Gömmel, Daniel; Jordan, Sophia; Masuch, Michael; Kühl, Alexander; Franke, Jörg (Proceedings of 2024 IEEE Wireless Power Technology Conference and Expo, WPTCE 2024, 2024)
Electric Road Systems (ERS) for electric vehicles seem to be a promising solution to increase the range of electric vehicles without having to use larger batteries. Therefore, the resonance circuits have to be deployed into the roadways very precise to ensure best transmission efficiency and no breakdowns due to insufficient installation. Beside the manufacturing and deployment processes, the product properties have to be adapted to the requirements of road construction technologies. The main objective of this paper is to use simulation results and practical validation of materials and systems to determine the thermal requirements of resonant coil circuits for ERS. From the construction technologies of asphalt roads as well as the operation of electric road systems, the resulting material requirements for the encapsulation are determined. By characterization of different insulation materials, simulation models on the thermal impact of the system components are derived. The models are validated through practical test setups. The results provide knowledge that can be used to optimize the product design to different use cases in operation as well as construction.
CRIS-Team Scopus Importer:2024-07-12
Keywords: Manufacturing; Simulation; Thermal Optimization; Wireless Power Transfer